2018
DOI: 10.1111/ggi.13305
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the activities of daily living, oral health‐related quality of life and dementia

Abstract: Most oral problems are not simply the outcome of aging, with oral hygiene management being the most important determining factor. Oral health problems can be prevented, and in order to improve the quality of life of older adults, attention must be paid to oral healthcare. Geriatr Gerontol Int 2018; 18: 943-949.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
(39 reference statements)
3
19
0
Order By: Relevance
“…Our regression and path analyses also showed that a decrease in ADL increased the possibility of cognitive impairment. Additionally, Pearson's correlation analysis showed that the two parameters of oral health (OHIP‐14 and GOHAI) were correlated with ADL, which supports the findings of previous studies …”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our regression and path analyses also showed that a decrease in ADL increased the possibility of cognitive impairment. Additionally, Pearson's correlation analysis showed that the two parameters of oral health (OHIP‐14 and GOHAI) were correlated with ADL, which supports the findings of previous studies …”
Section: Discussionsupporting
confidence: 89%
“…Many patients with cognitive impairment experience difficulties in managing their ADL, which may be a factor that complicates oral health management . In a population‐based study on elderly participants that analysed ADL and cognitive function using Cox proportional hazards regression models controlled for other covariates such as age and sex, it was concluded that ADL disability was a strong risk factor for dementia .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations